RANCANG BANGUN SISTEM BILLING BERBASIS WEB DI KLINIK DANDER MEDICAL CENTER - tegar wahyu yudha pratama (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2021)
Background: billing systems at the dander medical center clinic continue by hand all calculations and repayments for hospitalization, outkeeping ander still use Microsoft excel. Even payment bills still use shop/receipt to write down down here on the e-patient payment, hospitalization and emergency room. Subject and Methods: This research method of design research is a R&D with design using system development methods with SDLC. Results: implementing the system for electronic web-based outpatient medical records information that is consistent with the function and usefulness of each menu in the system. The keypad was also functioning properly. Counclusion: This research conclusion gives rise to a billing clinic's engineering application for dander medical center.